The Influence of Visual Uncertainty on Word Surprisal and Processing Effort - Ankener, Christine S.; Sekicki, Mirjana; Staudte, Maria (Frontiers in Psychology, 2018)
A word’s predictability or surprisal, as determined by cloze probabilities or language models (e.g.,Frank, 2013) is related to processing effort, in that less expected words take more effort to process (e.g., Hale, 2001; Lau et al., 2013). A word’s surprisal, however, may also be influenced by the non-linguistic context, such as visual cues: In the visual world paradigm (VWP), anticipatory eye movements suggest that listeners exploit the scene to predict what will be mentioned next (Altmann and Kamide, 1999). How visual context affects surprisal and processing effort, however, remains unclear. Here, we present a series of four studies providing evidence on how visually-determined probabilistic expectations for a spoken target word, as indicated by anticipatory eye movements, predict graded processing effort for that word, as assessed by a pupillometric measure (ICA). These findings are a clear and robust demonstration that the non-linguistic context can immediately influence both lexical expectations, and surprisal-based processing effort.